2019
DOI: 10.1259/bjr.20190270
|View full text |Cite
|
Sign up to set email alerts
|

Complexity metrics for IMRT and VMAT plans: a review of current literature and applications

Abstract: Modulated radiotherapy with multileaf collimators is widely used to improve target conformity and normal tissue sparing. This introduced an additional degree of complexity, studied by multiple teams through different properties. Three categories of complexity metrics were considered in this review: fluence, deliverability and accuracy metrics. The first part of this review is dedicated to the inventory of these complexity metrics. Different applications of these metrics emerged. Influencing the optimizer by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 84 publications
2
95
0
2
Order By: Relevance
“…35 The major significant difference between FF and FFF beams was rics. 36 Then, with respect to the trade-off between plan complexity and the dosimetric accuracy of the treatment delivery, we performed a "pre-treatment" dose verification of all plans to assess the accuracy in dose delivery. Despite the complexity of these plans, the results of dosimetric verification confirmed the deliverability of our SBRT-VMAT technique and its reliability for clinical applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The major significant difference between FF and FFF beams was rics. 36 Then, with respect to the trade-off between plan complexity and the dosimetric accuracy of the treatment delivery, we performed a "pre-treatment" dose verification of all plans to assess the accuracy in dose delivery. Despite the complexity of these plans, the results of dosimetric verification confirmed the deliverability of our SBRT-VMAT technique and its reliability for clinical applications.…”
Section: Resultsmentioning
confidence: 99%
“…All these aspects contribute to a more complex fluence and may affect the dosimetric accuracy of actual delivery. Many studies reported that plan complexity indices are correlated with delivery accuracy and the quality assurance metrics 36 . Then, with respect to the trade‐off between plan complexity and the dosimetric accuracy of the treatment delivery, we performed a “pre‐treatment” dose verification of all plans to assess the accuracy in dose delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Possible correlations between measured dose deviations and the modulation complexity score applied to VMAT (MCSv), MLC leaf travel (LT), the average change in dose rate per control point (ΔDR/cp), monitor units pr. Gy (MU/Gy), and homogeneity index for the PTV (HI) were investigated . A lower MCSv indicates a plan with more modulation, while a MCSv of 1 indicates no modulation, that is, a static, open field.…”
Section: Methodsmentioning
confidence: 99%
“…While measurement‐based PSQA is regarded as the most accurate method of assessing delivery accuracy, 1,3 extensive literature exists in developing pre‐treatment quality assurance (PTQA) tools for this purpose by quantifying plan complexity as indications of dose agreement. These complexity metrics can be used to describe the degree of dose modulation in a treatment.…”
Section: Introductionmentioning
confidence: 99%
“…An increased modulation often leads to increased uncertainty in dose because of the limitations of accurately modeling linac components such as MLC tongue and groove which affects the interleaf leakage, and leaf offset between the calculated rounded leaf tip value and the measured one. Generally, higher degrees of modulation suggest more complex treatments, and consequently increased uncertainty in delivery 3–12 …”
Section: Introductionmentioning
confidence: 99%